Case Report: Sliding gouty tophi: a case of dynamic ultrasound diagnosis of carpal tunnel syndrome - Qu, Chenchen; Deng, Heping; Lu, Bo; Mi, Yaru; Ye, Hui; Zhu, Yaru (Frontiers in Surgery, 2025)
Carpal tunnel syndrome (CTS) caused by gouty tophi is a rare clinical condition. In this case, ultrasonography clearly identified gouty tophi deposited within the superficial flexor tendon of the right middle finger, resulting in tendon thickening. The thickened tendon was constrained by the transverse carpal ligament, leading to restricted finger movement. Additionally, when the finger was extended, the thickened tendon slid beneath the transverse carpal ligament, triggering severe symptomatic episodes of CTS. This observation provided direct evidence of the underlying etiology of CTS in this patient.